The Impact of an Experimental Guaranteed Income on Crime and Violence. (18th March 2020) - Calnitsky, David; Gonalons-Pons, Pilar
Abstract: Would unconditional cash payments reduce crime and violence? This paper examines data on crime and violence in the context of an understudied social experiment from the late 1970s called the Manitoba Basic Annual Income Experiment, or Mincome. We combine town-level crime statistics for all medium-sized Canadian Prairie towns with town-level socio-demographic data from the census to study how an experimental guaranteed income affected both violent crime and total crime. We find a significant negative relationship between Mincome and both outcomes. We also decompose total crime and analyze its main components, property crime and "other" crime, and find a significant negative relationship between Mincome and property crime. While the impact on property crime is theoretically straightforward, we close by speculating on the mechanisms that might link the availability of guaranteed annual income payments to a decline in violence, focusing on the mechanisms that shape patterns of inter-partner violence.